Answer: 3x+72 Step-by-step explanation: Let’s first simplify the equation 3(10x+9)−9(3x−5) You want to distribute first =(3)(10x)+(3)(9)+(−9)(3x)+(−9)(−5) =30x+27+−27x+45 And then combine like terms: =30x+27+−27x+45 =(30x+−27x)+(27+45) =3x+72 (answer) Log in to Reply

Answer: Let’s simplify step-by-step. 3(10x+9)−9(3x−5) Distribute: =(3)(10x)+(3)(9)+(−9)(3x)+(−9)(−5) =30x+27+−27x+45 Combine Like Terms: =30x+27+−27x+45 =(30x+−27x)+(27+45) =3x+72 Log in to Reply

Answer:3x+72

Step-by-step explanation:Let’s first simplify the equation 3(10x+9)−9(3x−5)

You want to distribute first

=(3)(10x)+(3)(9)+(−9)(3x)+(−9)(−5)

=30x+27+−27x+45

And then combine like terms:

=30x+27+−27x+45

=(30x+−27x)+(27+45)

=3x+72 (answer)

Answer:Let’s simplify step-by-step.

3(10x+9)−9(3x−5)

Distribute:

=(3)(10x)+(3)(9)+(−9)(3x)+(−9)(−5)

=30x+27+−27x+45

Combine Like Terms:

=30x+27+−27x+45

=(30x+−27x)+(27+45)

=3x+72